Optimizing Intelligence Oversight in National Security Intelligence - Fernando, yudha; Runturambi, Arthur Josias Simon (The Republic of Indonesia Defense University, 2026)
The objective of this study is to formulate a good and accountable intelligence governance. At the same time, this is fundamental to a democratic state. Implementing this principle is crucial to preventing abuse of power and ensuring that intelligence activities are conducted responsibly. The object and purpose of this study are to identify the current position of the national security intelligence oversight system in Indonesia and provide suggestions for optimizing intelligence oversight. This study aims to balance national security needs with civil liberties and privacy, and facilitate reporting of suspicious activity. This study employed a descriptive, qualitative approach. Primary and secondary data were obtained through a literature review of intelligence oversight and related regulations, in-depth interviews, and focus group discussions. These data were then validated through method and source triangulation techniques, peer debriefing, and member checking before being analyzed using Miles and Huberman's qualitative analysis method. The theory used in this study is the Intelligence Oversight Theory, a legal and procedural framework that ensures all intelligence activities comply with laws, executive orders, and human rights. The results of the study show that, to optimize the layered intelligence oversight system, the involvement of civil society entities and the establishment of a new independent oversight entity are needed. Meanwhile, to optimize the effectiveness of intelligence supervision, it is necessary to add three indicators: timeliness, cost accuracy, and measurement accuracy.